Study Course of Mother-Tongue: Relevant Aspects - Makarovna Aleksandrova, Olga; Nurgainovna Dobrotina, Irina; Nikolaevna Gosteva, Yulia; Vladimirovna Uskova, Irina; Pavlovna Vasilevykh, Irina; ., . (International Journal of Engineering and Technology, 2018)
The article analyzes relevant aspects of the Russian language syllabus for schools in the light of the study content being presented in reference documents while taking into consideration historical background and context. Based on modern methods of scientific research, experimental work and experience in designing the study content of the Russian language course the authors conclude that relevant aspects of the school course syllabus come The article analyzes relevant aspects of the Russian (native) language syllabus for schools in the light of the study content being presented in reference documents while taking into consideration historical background and context. The article aims at drawing attention to peculiarities of designing the study content of the mother-tongue course formed at the edge of the 19-20th centuries which are still fruitfully developing nowadays. Based on modern methods of scientific research, experimental work and experience in designing the study content of the Russian (native) language course the authors conclude that relevant aspects of the school course syllabus come down to progressive movement towards competence approach in the presentation of the course’s content; actualization of its supra-subject (meta-subject) function; implementation of its axiological aspect; orientation of the school course on the development of the child's personality, one’s cognitive and creative abilities, as well as spiritual and social experience. The research resulted in methodical system aimed at meeting axiological, thematic and meta-subject challenges during the students’ broad-ranging activities.